2023
DOI: 10.1097/hc9.0000000000000180
|View full text |Cite
|
Sign up to set email alerts
|

Rising alcohol-associated liver disease–related mortality rates in the United States from 1999 to 2022

Abstract: We examined trends in alcohol-associated liver disease (ALD)–related mortality in the United States from 1999 to 2022, focusing on sex, racial differences, and specific age groups. We analyzed age-adjusted mortality rates for ALD-related deaths using the CDC WONDER database and assessed differences between sex and racial groups. ALD-related mortality rates increased significantly between 1999 and 2022, with a more pronounced increase in females. White, Asian, Pacific Islander (AAPI), and American Indian or Ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In terms of sex, multiple studies have pointed out the increasing burden of ALD and AUD to a greater extent in females than in males. [34] , [35] , [36] In contrast, some studies found that the burden of ALD and AUD were lower in women, possibly owing to substantially lower levels of alcohol consumption. [37] , [38] , [39] The differences could be attributed to variations in the population of the studies, with some mainly involving younger adults or overall populations, whereas this study focused on the elderly.…”
Section: Discussionmentioning
confidence: 98%
“…In terms of sex, multiple studies have pointed out the increasing burden of ALD and AUD to a greater extent in females than in males. [34] , [35] , [36] In contrast, some studies found that the burden of ALD and AUD were lower in women, possibly owing to substantially lower levels of alcohol consumption. [37] , [38] , [39] The differences could be attributed to variations in the population of the studies, with some mainly involving younger adults or overall populations, whereas this study focused on the elderly.…”
Section: Discussionmentioning
confidence: 98%
“…7 Conversely, mortality related to alcoholic liver diseases was already on the rise before the pandemic, 7 and this increase became even more pronounced in 2020-2021. 8,20,26,27 This may be attributed to increased alcohol consumption, social isolation, and disruptions in healthcare. The data from Northeastern Italy presented here are the first outside of the US to assess the impact of DAA therapy on mortality at the population level.…”
Section: Yearmentioning
confidence: 99%
“…Alcohol-associated liver disease (ALD) presents with different phenotypes ranging from steatosis to the development of steatohepatitis, and in some cases, liver cirrhosis and hepatocellular carcinoma. ALD accounts for a significant portion of adult morbidity and mortality statistics [5]. Currently, there are no approved targeted therapies able to halt the progression of the disease, therefore alcohol cessation remains the first-line treatment in all stages of ALD [6].…”
Section: Introductionmentioning
confidence: 99%